Antibacterial and anti-inflammatory ultrahigh molecular weight polyethylene/tea polyphenol blends for artificial joint applications. Issue 45 (28th October 2020) - Ren, Yue; Wang, Fei-Yu; Chen, Zi-Jian; Lan, Ri-Tong; Huang, Ren-Huan; Fu, Wan-Qun; Gul, Rizwan M.; Wang, Jing; Xu, Jia-Zhuang; Li, Zhong-Ming
Abstract : A facile and efficient method to fabricate antibacterial and anti-inflammatory artificial joint with tea polyphenols. Abstract : Periprosthetic joint infection (PJI) is one of the main causes for the failure of joint arthroplasty. In view of the limited clinical effect of oral/injectable antibiotics and the drug resistance problem, there is a pressing need to develop antibacterial implants with therapeutic antimicrobial properties. In this work, we prepared a highly antibacterial ultrahigh molecular weight polyethylene (UHMWPE) implant by incorporating tea polyphenols. The presence of tea polyphenols not only improved the oxidation stability of irradiated UHMWPE, but also gave it the desirable antibacterial property. The potent antibacterial activity was attributed to the tea polyphenols that produced excess intracellular reactive oxygen species and destroyed the bacterial membrane structure. The tea polyphenol-blended UHMWPE had no biological toxicity to human adipose-derived stem cells and effectively reduced bacteria-induced inflammation in vivo . These results indicate that tea polyphenol-blended UHMWPE is promising for joint replacement prostheses with multifunctionality to meet patient satisfaction.